Respuesta :
Answer is: Kc for the reaction is 1·10¹³⁰.
Chemical reaction 1: SO₂(g) → O₂(g) + S(s); Kc₁ = 2,5 × 10⁻⁵³.
Chemical reaction 2: SO₃(g) → 1/2 O₂(g) + SO₂(g); Kc₂ = 4,0 ×10⁻¹³.
Chemical reaction 3: 2S(s) + 3O₂(g) → 2SO₃(g); Kc₃ = ?.
We can get reaction 3 by summing reverse reaction multiply with and reverse reactio 2 multiply with two.
Kc₃ = (1/Kc₁²) · (1/Kc₂²) = 1/(2,5 × 10⁻⁵³)² · 1/(4,0 ×10⁻¹³)².
Kc₃ = 1,6·10¹⁰⁵ · 6,25·10²⁴ = 1·10¹³⁰.
Chemical reaction 1: SO₂(g) → O₂(g) + S(s); Kc₁ = 2,5 × 10⁻⁵³.
Chemical reaction 2: SO₃(g) → 1/2 O₂(g) + SO₂(g); Kc₂ = 4,0 ×10⁻¹³.
Chemical reaction 3: 2S(s) + 3O₂(g) → 2SO₃(g); Kc₃ = ?.
We can get reaction 3 by summing reverse reaction multiply with and reverse reactio 2 multiply with two.
Kc₃ = (1/Kc₁²) · (1/Kc₂²) = 1/(2,5 × 10⁻⁵³)² · 1/(4,0 ×10⁻¹³)².
Kc₃ = 1,6·10¹⁰⁵ · 6,25·10²⁴ = 1·10¹³⁰.
Answer:
SO2(g) ---> O2(g) + S(s)
Kc=2.5 x 10^-53
we get ::
2 O2(g) + 2 S(s) ---> 2 SO2(g)
Kc1 = (1 / (2.5 x 10^-53))^2
SO3(g) ---> 1/2 O2(g) + SO2(g)
Kc=4.0 x 10^-13
we get :
O2(g) + 2 SO2(g) --> 2 SO3
Kc2 = (1 / 4.0 x 10^-13) ^2
2 O2(g) + 2 S(s) ---> 2 SO2(g) , Kc1
O2(g) + 2 SO2(g) --> 2 SO3 , Kc2
----------- ----------------- ---------- -------- +
2 S(s) + 3 O2(g) ---> 2 SO3(g) Kc = Kc1 . Kc2
Kc = (1 / (2.5 x 10^-53))^2 (1 / 4.0 x 10^-13)^2
Kc = 1.0 10^130
SO2(g) ---> O2(g) + S(s)
Kc=2.5 x 10^-53
we get ::
2 O2(g) + 2 S(s) ---> 2 SO2(g)
Kc1 = (1 / (2.5 x 10^-53))^2
SO3(g) ---> 1/2 O2(g) + SO2(g)
Kc=4.0 x 10^-13
we get :
O2(g) + 2 SO2(g) --> 2 SO3
Kc2 = (1 / 4.0 x 10^-13) ^2
2 O2(g) + 2 S(s) ---> 2 SO2(g) , Kc1
O2(g) + 2 SO2(g) --> 2 SO3 , Kc2
----------- ----------------- ---------- -------- +
2 S(s) + 3 O2(g) ---> 2 SO3(g) Kc = Kc1 . Kc2
Kc = (1 / (2.5 x 10^-53))^2 (1 / 4.0 x 10^-13)^2
Kc = 1.0 10^130